Acute Multifocal Haematogenous Osteomyelitis with Sepsis in a 10 Years Old Child Caused by Methicillin-Resistant Staphylococcus aureus: A Case Report - Joshi, Sachindra Raj; Karki, Dipesh; Rajbhandari, Tarun; Barnawal, Satish Prasad (Nepal Orthopaedic Association Journal, 2025)
BACKGROUNDAcute Haematogenous Osteomyelitis is common in children, but the multifocal form, Acute Multifocal Osteomyelitis, is rare and has the potential to involve multiple bones. The usual organism causing acute osteomyelitis in children is Staphylococcus aureus; however, the presence of methicillin-resistant Staphylococcus aureus (MRSA) strains in the community has been associated with increased disease severity. Also, the disease might advance rapidly and result in severe morbidity and mortality if not treated early, but many factors relate to delayed treatment in our part of the world. We present a 10-year-old girl from the rural mountain region of Nepal with acute multifocal haematogenous osteomyelitis with sepsis caused by methicillin-resistant Staphylococcus aureus (MRSA).